Evaluation of a Multi-Site Demonstration of Collaborations to Address Domestic Violence and Child Maltreatment in the United States, 2001-2006 - Griffith, Janet ([Verlag nicht ermittelbar], 2010)
The current study was a national evaluation that examined the effects of implementing The Greenbook recommendations on collaboration, systems change, and practice within and across the three primary systems of child welfare agencies, courts, and domestic violence service providers. The national evaluation utilized data collected through stakeholder surveys, direct service worker surveys, child welfare case file reviews, and site visit interviews between 2001 and 2006. The purpose of the national evaluation was to develop and implement a strategy for gaining a formative understanding of sites' planning and implementation processes and a summative assessment of the impact of such work on communities, systems, and families. Part 1 (Stakeholder Survey Data) includes variables on the respondent's level of involvement in the organization and barriers to implementing Greenbook initiatives. The baseline stakeholder survey was conducted in 2002 with a total of 86 respondents across sites, and follow-up data were collected three years later (2005) with a total of 62 respondents. Part 2 through Part 7 (Direct Service Worker, and Supervisor Data) include variables on the respondents' race, gender, and length of time at the child welfare agency, court, or domestic violence service provider. Respondents are asked about the hours of training received over the past year, the presence of written reporting guidelines, screening tools, and working relationships with the other agency types. The baseline direct service worker survey was conducted after the end of the demonstration planning period (2003) with a total of 275 respondents across sites, and follow-up data were collected two years later (2005) with a total of 224 respondents. Part 8 (Case Abstractions Data) includes variables on substantiated cases of child maltreatment, risk factors contributing to maltreatment attributed to the mother, the father, or other caregiver, documentation of domestic violence and services provided to the victims and perpetrators. A random sample of substantiated cases of child maltreatment was reviewed in each site at the beginning of the demonstration initiative (2001) with a total of 616 case files reviewed across sites, after the end of the planning period (2003) with a total of 642 case files reviewed across sites, and toward the end of the implementation period (2005) with a total of 562 case files reviewed across sites. Part 9 (Site Visit Interview Notes Qualitative Data) includes questions on structure of services, policies and procedures, training, and the strengths and needs of the site. Site visits were conducted between January 2001 and June 2006 with interviewers with at least one collaborative member from each of the three primary systems (child welfare agency, courts, domestic violence service provider).